Jobs, Skills and Incomes in Ghana: How was poverty halved? - Nsowah-Nuamah, N; Teal, F; Awoonor-Williams, M (CSAE (University of Oxford), 2010)
Poverty has halved in Ghana over the period from 1991 to 2005. Our objective in this paper is to assess how far this fall was linked to the creation of better paying jobs and the increase in education. We find that earnings rose rapidly in the period from 1998 to 2005, by 64% for men and by 55% for women. While education, particularly at the post secondary level, is associated with far higher earnings there is no evidence that the increase in earnings that occurred over the period from1998 to 2005 is due to increased returns to education or increased levels of education. In contrast there is very strong evidence, for all levels of education, that the probability of having a public sector job approximately halved over the period from 1991 while the probability of having a job in a small firm increased very substantially. In 1991/92 a male worker with secondary education had a 7 per cent probability of being employed in a small firm, by 2005/06 this had increased to 20 per cent which was higher than the probability of being employed by the public sector. Employment in small firms, which is the low paying occupation within the urban sector, increased from 2.7 to 6.7 percent of the population, an increase from 225,000 to 886,000 employees. Jobs in total have been increasing in line with the population but the proportion of relatively low paying ones increased markedly from 1998/99 to 2005/06. The rises in income that occurred over this period were due almost entirely to increases in earnings rates, for given levels of education, across all job types particularly among the unskilled. Why unskilled earnings rates rose so rapidly is unclear.